A PERSON-CENTERED INDEX OF AGING WELL AND ITS DETERMINANTS IN NORTH AMERICA. (16th November 2018) - Belanger, E; Wu, Y; Legkaya, Y; Thompson, M; Pirkle, C; Perez-Zepeda, U; Castrejon-Perez, R; Moullec, G
Abstract: Positive models of aging, including aging well, and active, healthy or successful aging models, are increasingly receiving attention from gerontologists and geriatricians. Yet important challenges remain in defining and measuring positive aging consistently and in line with older adults' perspectives for research, practice and policy purposes. The primary objective of this study was to develop a person-centered index of aging well that integrates previous research on lay perspectives, and to examine the social determinants of this index in an effort to promote health and social policies that maximize the well being of older adults. We conducted secondary analyses of large national databases collected in 2014 across North America, namely the U.S. Health and Retirement Study (N= 3, 463), the Canadian Longitudinal Study on Aging (N=18, 553), and the Mexican Healthy Aging Study (N=6, 456). Starting from qualitative evidence in all three countries, we constructed a composite index capturing lay perspectives. The index proposed is a continuous score, and contains health-related components such as disability in activities of daily living and mobility, pain, self-rated health, and cognitive function, as well as psychosocial components such as mood, productive activities, social relations, and life satisfaction. Mean scores on the index were 69.9(SD 14.2) in the US, 56.34 (17.03 SD) in Mexico, and 79.8 (SD 10.7) in Canada. Men had significantly higher scores in all countries. While there were notable differences in effect sizes, income, education, tobacco use, and physical exercise were important determinants of aging well across North American countries.